(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
Job ads have long been of interest to researchers concerned with the issue of native speakerism as they may constitute the initial and often insurmountable barrier to career opportunities for non-native teachers of English. This article explores the requirements that potential employers place before teachers of English in job ads posted on a major Polish job offer aggregate. By means of Thematic Analysis, this research sheds more light on the demands that teachers of English need to meet in the Polish job market and investigates whether job ads in Poland disseminate the ideology of native speakerism. The results show employers may overemphasise personal qualities, such as character traits and attitudes, compared to qualifications and skills. Although the majority of job ads explored did not overtly perpetuate the ideology of native speakerism, further research is necessary to understand the extent of this issue fully.